Lithuania Country Report - Krupavicius, Alvis; Zvaliauskas, Giedrius (2000)
If we would like to find out a single and most important feature of individual political behaviour in Eastern and Central Europe in 1989, of course, it should be an unconventional political activity and direct political actions. Altogether, a marathon of referendums in 1992- 1996, instead of encouraging of participatory culture, stimulated the protest behaviour in Lithuania's politics, when citizens became politically active only if they have had an object to oppose certain decisions rather than they were interested to support positively one or another position, or discuss different political alternatives. In general, the basis of electoral mobilization was rather protest politics than politics of participation and support from the very beginning of re-democratization in Lithuania.